2010
DOI: 10.1111/j.1530-0277.2010.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Resource Optimization in Male Alcoholics: N400 in a Lexical Decision Paradigm

Abstract: Background Event Related Potential (ERP) studies have highlighted some measures, notably P3 amplitude, that are associated with both state and trait deficits in alcoholism, while studies examining N400 amplitude in alcoholism are few. The present study aims to examine changes in the N400 component, an electrophysiological correlate of semantic priming, in event-related potentials from a lexical decision task in 87 alcohol dependent subjects and 57 community controls. Method Each subject was presented with 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 93 publications
(118 reference statements)
0
13
1
Order By: Relevance
“…In one study a lexical decision task was employed to study 87 alcohol dependent subjects and 57 community controls. In that study alcohol dependent participants were found to display less attenuation of the N400 response to primed words when compared to unprimed words (Roopesh et al, 2010). Additionally, similar findings were observed for a group of high risk offspring of alcoholics as compared to low risk children where the same finding of a lack of attenuation for primed words was observed (Roopesh et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In one study a lexical decision task was employed to study 87 alcohol dependent subjects and 57 community controls. In that study alcohol dependent participants were found to display less attenuation of the N400 response to primed words when compared to unprimed words (Roopesh et al, 2010). Additionally, similar findings were observed for a group of high risk offspring of alcoholics as compared to low risk children where the same finding of a lack of attenuation for primed words was observed (Roopesh et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…Electrophysiological studies of individuals with alcohol dependence and subjects with a family history of alcoholism have demonstrated that deficits in a number of event-related potential (ERPs) components, with robust findings observed for late positivities (300-450 msec) (this literature is very large and there are a number of excellent reviews, see Begleiter and Porjesz, 1999, Porjesz and Begleiter, 2003, Porjesz et al, 2005, Campanella et al, 2009]) and more recently late negativities (300-650 msec) as well (see Roopesh et al, 2009, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Reduced N4 amplitude of the difference waveform between primed and unprimed words has been reported (Nixon et al, 2002). Similarly, in a recent semantic decision task there was less attenuation of N400 amplitudes to primed words when compared to unprimed words in alcoholics, a phenomenon that was intact in the controls (Porjesz et al, 2002b; Roopesh et al, 2010) (Fig. 23.4).…”
Section: Chronic Alcoholism and Neuroelectrophysiologymentioning
confidence: 82%
“…Even though some evidence suggests that verbal skills are relatively well preserved in individuals with alcohol dependence (Oscar-Berman and Schendan, 2000; Parsons, 1987), ERP studies indicate deficits in semantic processing. Studies of abstinent long-term alcoholics indicate reduced N400 amplitudes, suggesting that such individuals do not benefit from priming induced by sentential or single-word paradigms (Ceballos et al, 2005; Nixon et al, 2002; Roopesh et al, 2010). Furthermore, similar priming deficiencies found in individuals with a family history of alcoholism (Roopesh et al, 2009) suggest a genetic component (Almasy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%